Chapter Rulership and the Gods: The Role of Cultic Institutions in the Late Bronze to Iron Age Transition in Anatolia and Northern Syria - d'Alfonso, Lorenzo (Studia Asiana, 2023)
This paper aims to demonstrate that cults and cultic institutions are a crucial element for understanding the processes producing different regional outcomes after the fall of the Hittite empire. In this paper, cults are understood as normative cosmic forces defining tempo and worldview of ancient societies. Cultic institutions can be identified as physical spaces defined by purity, charged with real and symbolic value, and led by specialists whose competence is recognised by the community. Instead of being a by-product of political complexity, they are a driving force behind the power dynamics because they are perceived as such in a bottom-up perspective, but also often by main political actors in search of legitimation of their power. This paper examines the interconnections between cultic and political institutions in the territory under the Hittite empire and in the same space after the empire's demise. We aim to distinguish between processes of resilience, reorganisation, and transformation as they occurred in particular micro-regions previously controlled by the empire, including the Upper Euphrates, South-Central Anatolia, North-Central Anatolia, Cilicia, and the Northern Levant; this will demonstrate both the importance of such a micro-regionally defined study, as well as the shared coincidence of cultic and political institutional change. It will become evident that cultic continuity coincided with the resilience of political institutions, and changes in the cultic landscape corresponded to political reorganisations or transformations in post-Hittite Anatolia and north Syria.